Not Just a Complaint: Students’ Solidarity as a Social Function in the Academic World - Fitria, Rachmi; Hufad, Achmad; Achdiani, Yani; Hasya, Vila; Azhar, Fina Aprilianti; Putri, Hariza Adia; Suparwanto, Ahmed Dipa (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
In undergoing lectures, of course, it cannot be separated from academic demands, sometimes these demands make students have excessive pressure that disrupts their daily lives. With this, students make confiding as a form of solving their academic problems because when they tell stories they will feel similarities in feelings and situations. The purpose of this study is to analyze how student solidarity is formed due to problems such as academic pressure. The theory used by Emile Durkheim's Functionalism theory is in line with Emile Durkheim's Functionalism theory where when a person cannot carry out his daily activities, the social function in his life becomes dysfunctional. In addition, it discusses the relevance of the derivative concept of Emile Duekheim's Functionalism theory, namely Mechanical Solidarity where a person becomes a group because of feelings and situations of compatibility. The method used is qualitative method with data collection through interviews with active students and literature studies. The research shows that the solidarity that is grown in the academic world is problem solving such as academic pressure because it raises motivation such as learning and discussion together even, because of this solidarity, someone gets to know each other better.